Spiritualitas Islam sebagai Landasan Regulasi Hukum Ekonomi Syariah; Studi Integratif Teori dan Praktik - Harahap, Elly Warnisyah; Latifah, Siti (IAIN Langsa, 2024)
This article aims to explore Islamic spirituality as the fundamental basis for the formulation of Sharia economic law regulations, adopting an approach that integrates theory and practice. This research is categorized as library research with a qualitative approach and utilizes descriptive analysis. Primary data were sourced from scientific journals published in the last ten years, while secondary data were obtained from books and related digital references. Data validity was ensured through triangulation, with the analysis process conducted inductively, moving from general data to specific conclusions. The study concludes that Islamic spirituality plays a central role in shaping the ethical values underpinning Sharia economic law regulations. This spiritual dimension not only guides economic actors to balance material and non-material interests but also ensures the sustainability of divine values in modern economic practices. The integration of theory and practice through this approach produces a regulatory framework that is not only normative but also practical in its application.